Analisis Kondisi Fisik Atlet Sepak Bola Persila Academy U17 Lombok Timur - Prasetyo, Muhammad Teguh; Hamzah, Hamzah; Ari, M. Azy' (Universitas Hamzanwadi, 2024)
The purpose of this research and development is to assess the physical condition of Persila Academy U-17 athletes. The method used in this research is descriptive quantitative. The sample withdrawal in this study used the total sampling method with the number of athletes totaling 20 players. The data analysis used is descriptive quantitative. The aspects assessed in this study include speed, abdominal muscle strength, agility, cardiovascular endurance and leg muscle explosiveness. The results showed that the abdominal muscle strength aspect was in the good category with a percentage of 35%, the agility aspect was in the average category with a percentage of 70%, the cardiovascular endurance aspect was in the average category with a percentage of 40%, the limb muscle explosive power aspect was in the very good category with a percentage of 30%. The conclusion in this study is that the physical condition of Persila Academy U-17 athletes is in the good category. Overall, players who have good physical condition will not only improve the quality of their game, but also reduce the risk of injury, increase the body's efficiency in using energy, and can last longer in matches with optimal performance.